Pemodelan Endapan Epitermal Sulfidasi Rendah Berdasarkan Interpretasi Data Magnetik di Daerah Wonosidi - Ahmad Hanafi; Ajimas Pascaning Setiahadiwibowo; Joko Soesilo; Firdaus Maskuri (Universitas Negeri Gorontalo, 2022)
The mineralization in the Pacitan area is generally a quartz vein zone and disseminated in the altered rock zone close to the quartz vein zone. The magnetic method is a geophysical method used to identify subsurface conditions based on the magnetic properties of rocks. This study aims to identify low sulfidation epithermal deposits based on the interpretation of magnetic data. Previous research put the existence of mineralization in the form of malachite, azurite, and pyrite in the study area. Then a geomagnetic survey was conducted to build a subsurface model helpful in knowing the widening and geometry of existing mineral deposits. The study used 118 geomagnetic measurement points in the 1.5 km x 1.5 km area by the gridding method, and the distance between points was 150 m. Apart from that, a derivative tilt filter and analytic signal were used to analyze the controller structure. The study's results, namely, there are three main faults, two faults oriented almost northwest-southeast and one fault oriented almost northeast-southwest, which are thought to be heretical mineralization controllers. And there are two patterns of high magnetic anomaly values in response to dacitic intrusion in the southwest and andesite intrusion in the eastern part of the telltale region, which is thought to affect the presence of alteration and mineralization in the study area.